2020
DOI: 10.1136/bmjdrc-2019-001033
|View full text |Cite
|
Sign up to set email alerts
|

Combined therapy of photobiomodulation and adipose-derived stem cells synergistically improve healing in an ischemic, infected and delayed healing wound model in rats with type 1 diabetes mellitus

Abstract: ObjectiveWe assessed the therapeutic effects of photobiomodulation (PBM) and adipose-derived stem cell (ADS) treatments individually and together on the maturation step of repairing of a delayed healing wound model in rats with type 1 diabetes mellitus (DM1).Research design and methodsWe randomly assigned 24 rats with DM1 to four groups (n=6 per group). Group 1 was the control (placebo) group. In group 2, allograft human ADSs were transplanted. Group 3 was subjected to PBM (wavelength: 890 nm, peak power outpu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(51 citation statements)
references
References 51 publications
(73 reference statements)
0
51
0
Order By: Relevance
“…However, T2D is developed when the body cannot properly respond to insulin. The most common type of diabetes is T2D, which consists about 85% to 95% of diabetic cases throughout the world (Ebrahimpour-Malekshah et al, 2020;Kulcsar et al, 2019). Etiologically, T2D is highly linked to obesity as well as the outcomes of chronic inflammation caused by excess adipose tissue.…”
Section: The Role Of Diabetes Mellitus and Hypertension In Acute Respmentioning
confidence: 99%
“…However, T2D is developed when the body cannot properly respond to insulin. The most common type of diabetes is T2D, which consists about 85% to 95% of diabetic cases throughout the world (Ebrahimpour-Malekshah et al, 2020;Kulcsar et al, 2019). Etiologically, T2D is highly linked to obesity as well as the outcomes of chronic inflammation caused by excess adipose tissue.…”
Section: The Role Of Diabetes Mellitus and Hypertension In Acute Respmentioning
confidence: 99%
“…Our results also showed a significant increase in cell viability, corresponding to the results observed in a similar study by de Villiers et al [ 31 ], who observed an increase in cell viability in isolated ADSCs and a commercial ADSC cell line irradiated at a wavelength of 636 nm and a fluence of 5 J/cm 2 . Ebrahimpour-Malekshah et al irradiated diabetic mice with an infected (MRSA) ischemic wound with or without transplanted ADSCs at 890 nm (power 80 W; pulse frequency 80 Hz; pulsed duration 180 ns; duration of exposure 200 s; power density 0.001 W/cm 2 ; and energy density 0.2 J/cm 2 ) 6 days per week for 16 days [ 39 ]. There was a significant decrease in microbial flora and inflammatory response and a significant increase in wound closure rate and strength and angiogenesis in all treated mice; however, it was found that PBM together with transplanted ADSCs showed superior results as compared to PBM and ADSC transplantation alone [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, in our lab, we have engrafted healthy AD-MSC cells into wounds of diabetic rats [23,26]. However, in the current probe, we engrafted preconditioned diabetic AD-MSC with PBM into wounds of diabetic rats.…”
Section: Introductionmentioning
confidence: 90%
“…We photographed the wounds on days 0, 4, 8, 12, and 16 and measured the wound surface area by ImageJ software (NIH, USA). The wound closure rate was calculated as follows [26]. Â Surfacearea at day 0 − surfacearea at day X ð Þ = surfacearea at day 0 Â 100%:…”
Section: Wound Closure Ratementioning
confidence: 99%